Effect of Bottle Storage on Colour, Phenolics and Volatile Composition of Malvasia and Moscato White Wines - Del Caro, A.; Piombino, P.; Genovese, A.; Moio, L.; Fanara, C.; Piga, A. (South African Journal of Enology and Viticulture, 2016)
The effect of bottle storage on the colour, phenolics and volatile composition of Malvasia and Muscat wines obtained from grapes grown in Sardinia was evaluated. Colour was evaluated by UV-VIS spectrophotometry and by tristimulus colorimetry. Polyphenols were analysed by UV-VIS spectrophotometry and HPLCDAD. GC/MS was used to identify and quantify the content of free and bound volatile compounds. As expected, the absorbance values at 420 nm increased significantly for both wines during storage, due to oxidative browning, while difference in colour (DE*) from the beginning of storage and after 18 months was more intense in the Muscat wine than in the Malvasia wine. A significant decrease was observed in different phenolic compounds over time, especially in the Malvasia wine. In-bottle storage for 18 months at 20°C in the dark resulted in a significant decrease in all the classes of free and bound volatiles. These finding enhance knowledge regarding the effects of bottle storage on Muscat and Malvasia wines. This is of interest because, rather surprisingly, this topic has been poorly investigated in relation to these two varieties.